(untitled) (Journal of Geography and Environmental Management, 2018)
The article considers the geographical aspects of the economic assessment of agricultural lands of Almaty agglomeration. Specificity of agricultural land use depends on natural and landscape features of Kazakhstan. A scientifically justified territorial organization of agricultural production should be implemented on the basis of accounting for both component-wise conditions and assessment criteria for natural-landscape heterogeneity. Analyzing the diversity of types of natural landscapes on the territory of the Almaty agglomeration, it can be noted that the economic and geographical assessment of suburban lands is impossible without taking into account the local approach. Each type, species, unit, district, area of a specific landscape has its own specific characteristics, differently react to various anthropogenic impacts, thereby differing in the economic value of the territory. As a result of the study, methodological recommendations for improving the economic and geographical assessment of land resources in the suburban areas of the Almaty agglomeration were developed.